Psychostimulants misuse: a challenge for public health - Orozco-Muñoz, Javier S. (2025)
Objective: Develop a narrative synthesis about a global public health problem known as psychostimulant misuse. Materials and methods: Narrative literature review using six databases from January 2010 to December 2023, under PRISMA recommendations. Results: The psychostimulants consumption, including nootropics and energy drinks, is increasing worldwide, creating a public health problem. Substances such as methylphenidate, modafinil and piracetam are used without a prescription to improve academic and work performance, as well as energy drinks, led by caffeine. The increase in their production and consumption has been associated with adverse cardiovascular and neurological effects. Conclusion: The indiscriminate consumption of psychostimulants has been associated with adverse cardiovascular and neuropsychiatric effects, so scientific and political interest should be encouraged in the construction of research projects and educational programs to prevent their abuse.